MENDESAIN ULANG SISTEM YUDICIAL REVIEW TERHADAP PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Hady, Nuruddin (JURNAL KONSTITUSI, 2011)
Judicial Review is the testing effort by the judicial institutions of the laws that were set by the legislative branch of power, and executive. This is giving authority to the judge as an application of the principle of checks and balances based on separation of powers system of the country. In principle, the testing system of laws and regulations in Indonesia can be distinguished between the concept of testing legislation under the laws of the laws under the authority of the Supreme Court (MA) and testing the concept of laws against the Constitution which is the authority Constitutional Court (MK). However, there are weaknesses in the testing process of the legislation under laws that were tested by the Supreme Court, because in principle the authority of the Supreme Court just testing the laws and regulations under legislation against the law, and the Supreme Court can not test regulations under the 1945 Act directly. So the question then is, what if the law relied upon by the Supreme Court to examine the legislation under the law being applied is actually contrary to the 1945 Constitution. In addition, by placing the testing system of laws and regulations in Indonesia are located at the two institutions --- the Supreme Court and Constitutional Court, then in certain cases, be substantially decision may lead to overlapping of the decision made by the two agencies. Therefore, this article will focus on whether the testing system (yudicial Review) against the legislation in Indonesia is in practice so far has been pretty ideal, and have guaranteed the principle of legal certainty and sense of justice in society. Additionally, this article tries to give an idea to rearrange the need for testing the system against the legislation in Indonesia, with full authority to test the legislation in Indonesia to the Constitutional Court (MK), this idea is a process Ius Constituendum